Provitamin A activity in traditional foods from Black Sea Area countries - Sanches-Silva, A. (2013)
Introduction and objectives: Vitamin A is found in the form of retinol, retinal, retinoic acid or esters in animal sources, while in plant sources, it is in the form of provitamin A. Conjugated double bonds of carotenoids absorb light and are responsible for the brilliant colours of fruits and vegetables ranging from the yellow, orange to red. Moreover, they protect cells from oxidation and cellular damages, preventing of major chronic diseases. The aim of the present work was to determine the provitamin A activity in twenty eight traditional foods from six Black Sea Area countries (Bulgaria, Georgia, Romania, Russian Federation, Turkey and Ukraine). Method: Chromatographic separation was performed with a UPLC® BEH guard-column (2.1 x 5 mm, 1.7 µm particle size) and a UPLC® BEH analytical column (2.1 x 50 mm, 1.7 µm particle size). The mobile phases were a gradient of ultrapure water and acetonitrile/methanol (containing 0.05 M ammonium acetate)/dichloromethane (75:20:5, v/v/v). The flow-rate was 0.5 mL/min and carotenoids were monitored at 450 nm. The concentration of each carotenoid was expressed as µg per 100 g of edible portion. Provitamin A activity was expressed as µg of retinol equivalents (RE) or retinol activity equivalents (RAE) per 100 g of edible portion. Results: One RE is equivalent to 1 µg retinol or 6 µg β-carotene or 12 µg of other provitamin A carotenes whileone RAE is equivalent to 1 µg retinol, 2 µg β-carotene dissolved in oil, 12 µg β-carotene or 24 µg of other provitamin A carotenoids. From the 28 traditional foods analysed, 12 did not present any RE or RAE. All the foods of the oilseeds or oilseed products did not present provitamin A activity. The traditional food with highest provitamin A activity was plums jam (Romania), followed by kale soup (Turkey) and nettle sour soup (Romania). Conclusions: Although a great variability was found in the carotenoids content, some of the analysed traditional foods can be considered excellent sources of provitamin A. Due to the putative health benefits of these compounds, the consumption of those with higher provitamin A activity should be promoted. Acknowledgements: The research leading to these results has received funding from the European Community’s Seventh Framework Programme (FP7/2007-2013) under grant agreement n.º 227118.